2012
DOI: 10.1590/s0004-27302012000700006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and interleukin-6 secretion during the progression of type 1 diabetes

Abstract: Objective: To evaluate inflammatory, oxidizing, and reducing responses during the progression of type 1 diabetes mellitus (T1DM) in patients without chronic complications. Subjects and methods: Plasma antioxidant status, reactive oxygen species (ROS), and interleukin-6 (IL-6) were measured in 42 patients with T1DM and in 24 healthy subjects. Results: Significant increases were detected in the median values of ROS and IL-6 in patients with T1DM compared with healthy subjects (ROS ~ 4,836 vs. 2,036 RLU/min, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
2
14
1
2
Order By: Relevance
“…Controversial results are available in literature for this aspect as in one study none of the variables of lipid peroxidation showed any significant difference between T1DM patients and healthy controls while other studies in literature support the above findings. In the study by Reis et al, 2012 significant increase was detected in ROS and IL‐6 in patients with T1DM as compared to healthy subjects. In another study, children with type 1 diabetes demonstrated increased oxidative stress (lower SOD and GSH) when compared with healthy children) but their oxidative DNA damage (measured as DNA strand breaks) was not substantially altered compared with normal.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Controversial results are available in literature for this aspect as in one study none of the variables of lipid peroxidation showed any significant difference between T1DM patients and healthy controls while other studies in literature support the above findings. In the study by Reis et al, 2012 significant increase was detected in ROS and IL‐6 in patients with T1DM as compared to healthy subjects. In another study, children with type 1 diabetes demonstrated increased oxidative stress (lower SOD and GSH) when compared with healthy children) but their oxidative DNA damage (measured as DNA strand breaks) was not substantially altered compared with normal.…”
Section: Discussionmentioning
confidence: 90%
“…Results of present study are in similar trend as seen in the literature. One study by Reis et al, 2012 showed higher levels of IL‐6 in 42 T1DM patients than in 35 controls. In another study by He et al, 2014, the authors studied the levels of IL‐6, IL‐10 and TNF‐α in 35 children of T1DM and in 30 controls.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic elevations of circulating Interleukin-6 (IL-6) are observed in T1DM and T2DM (Pradhan et al, 2001; Reis et al, 2012). While transient increases in IL-6 are associated with SC proliferation (Toth et al, 2011), chronically elevated IL-6 is correlated with significant decrements in muscle health (e.g., cancer cachexia; Roubenoff, 1997; McKay et al, 2013).…”
Section: Mechanisms For Altered Satellite Cell Function In Diabetes Mmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 21 immune complications [59][60][61]. Therefore, diabetes is accompanied by high free radical levels in the blood and spleen (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%